Integrating Genre-Based and Collaborative Approaches to Foster Reading Literacy in Vocational High School - Jasmine Emerald Haque; Elih Sutisna Yanto (Universitas Islam Negeri Palopo, 2026)
This study explored the integration of Literature Circles within the Teaching and Learning Cycle framework to enhance reading comprehension of expository texts among vocational high school students. Employing a qualitative case study design, data were gathered through classroom observations, reflective journals, and semi-structured interviews with thirty-two students and analyzed using thematic analysis. The results revealed that each stage of the Teaching and Learning Cycle: Building Knowledge of the Field, Modeling of the Text, Joint Construction, and Independent Construction, played a distinctive role in supporting comprehension development, while Literature Circles provided collaborative opportunities for discussion, critical engagement, and shared meaning-making. The integration of both frameworks fostered cognitive, linguistic, and affective growth, transforming reading into a more engaging and student-centered process. Challenges such as limited technical vocabulary and initial communication anxiety were progressively mitigated through teacher scaffolding and peer collaboration. Overall, the findings highlight that this hybrid approach offers a powerful pedagogical model for vocational EFL contexts by combining structure with learner autonomy, enhancing comprehension, motivation, and communicative confidence. The study contributes to the growing body of genre-based and collaborative learning research, offering practical implications for teachers aiming to implement integrative literacy instruction in vocational education.